PENGARUH CASA, CAR, LDR DAN BOPO TERHADAP ROA PADA PERUSAHAAN PERBANKAN DENGAN PERFORMA TERBAIK MOBILE BANKING TAHUN 2018 – 2021 - Sari Putri Pertiwi; Evi Dora Sembiring (Gapenas Publisher, 2023)
Corona Virus Disease 19 (Covid-19), has caused a lot of harm to various sectors, especially the banking financial sector, therefore banks must carry out risk mitigation carefully, and use creative strategies to deal with the current uncertain conditions, including the use of Digital Banking. To find out the impact of the corona, there are benchmarks before and after the pandemic period from the achievement of banking financial performance. This performance can be measured through Profitability, which is a reference for assessing a company's ability to earn profits according to a specified period. Profitability is assessed through Return On Assets (ROA). Factors that cause changes in bank profitability can be seen from internal factors, namely CASA (Current Account Saving Account), CAR (Capital Adequacy Ratio), BOPO (Operating Efficiency Ratio), LDR (Loan to Deposit Ratio). The research object is the 10 Top Digital Banking Commercial Banks with the 2018-2021 financial report period. Processing and analysis of data using SPSS application version 25.00 with multiple linear regression models. Based on the results of hypothesis testing, it was found that CASA, LDR, BOPO had an effect on ROA and CAR had no effect on ROA